2019
DOI: 10.32479/ijefi.8256
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion, Mobile Phone Diffusion, and Economic Growth; Evidence From Africa

Abstract: Whether finance enhances growth has continued to be a major debate among academics in the bids to drive economic growth and development. Hitherto, empirical studies focusing on Africa in addressing these issues for the expected regional sustainable growth are rare. This study applied structural equation modelling to simultaneously analyse mobile phones diffusion, financial inclusion, and economic growth in a panel of 32 African countries over the period from 2004 to 2016. The results provided evidence that fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Financial inclusion is important in reducing poverty and the realisation of inclusive economic growth [34,75,76]. According to Mustonziwa and Maposa [19], "In Zimbabwe, the levels of financial inclusion are moderate and mobile money is one of the critical contributors and the key driver to financial inclusion".…”
Section: Financial Inclusion and The Attainment Of Selected Sustainab...mentioning
confidence: 99%
“…Financial inclusion is important in reducing poverty and the realisation of inclusive economic growth [34,75,76]. According to Mustonziwa and Maposa [19], "In Zimbabwe, the levels of financial inclusion are moderate and mobile money is one of the critical contributors and the key driver to financial inclusion".…”
Section: Financial Inclusion and The Attainment Of Selected Sustainab...mentioning
confidence: 99%
“…To collect the data, three primary sources were used. Firstly, adopting from [25,84,85] which are contributing works of literature to this research, two economic growth variables from World Development Indicator (WDI) are utilised namely: GDP per capita and Per capita GNI. The economic growth indicators provide a comparative view of inclusive financial access influence across countries.…”
Section: Datamentioning
confidence: 99%
“…Besides, amid the recent enhancement of financial integration initiatives, little analytical work has been undertaken to regularly record updated developments in financial inclusion to help regulators to recognise areas where further policy measures are needed. By reflecting on accessibility in SSA countries, this article subscribes to the developing body of research on inclusive financing, as scholars such as [25] has termed the SSA region as the region with low inclusive financing. However, [26] found that finance inclusive access has the ability to mitigate earnings disparity in the sub-region.…”
Section: Introductionmentioning
confidence: 99%
“…As a region, Africa has received a great deal of attention from scholars lately on the topic of financial inclusion (Adegbite & Machethe, 2020;Anarfo & Abor, 2020;Chinoda & Akande, 2019;Mustafa, Baita, & Usman, 2018;Nwafor, 2018;Oyinlola & Adedeji, 2019). Despite this growing interest, only a limited number of studies focus specifically on financial inclusion and growth at the ECOWAS regional economic bloc level (; Udo, Effiong, & Ogar, 2016;).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extending the above sub-Saharan perspective one step farther, are Chinoda and Akande (2019), Chinoda and Kwenda (2019), Popoola (2019), which look at financial inclusion within the context of the whole African continent. Indeed, while Popoola (2019) relies on panel data analysis of 36 African countries to investigate the link between financial inclusion and health shocks, the former two focus on the dynamics between technology, financial inclusion and economic growth in Africa.…”
Section: Literature Reviewmentioning
confidence: 99%